2016
DOI: 10.5114/pjp.2016.61452
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin accumulation and S33F mutation of CTNNB1 gene in colorectal cancer in Saudi Arabia

Abstract: Several risk factors associated with colorectal cancer (CRC) have been identified including β-catenin/CTNNB1 hotspot mutations. The levels of β-catenin within a cell are regulated via phosphorylation of the N terminus of β-catenin by GSK-3β. Thus far three serines (S33, 37, 45) and one threonine (T41) are considered to be the substrates for GSK-3β phosphorylation. In the present investigation an attempt was made to study the role of β-catenin mutations in exon-3 in 60 colorectal cancer patients from Kingdom of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Corresponding non-tumorous tissue did not reveal a mutation. Our finding comprehends the previous study carried out by Alomar and colleagues which screened CTNNB1 gene in 60 colorectal cancer patients from Kingdom of Saudi Arabia (KSA) and revealed an activating mutation (S33F) in one of the tumor samples [52]. Our observations also analyzed the grade of β-catenin protein of the CTNNB1 gene in colorectal cancer in Pakistani population.…”
Section: Discussionsupporting
confidence: 88%
“…Corresponding non-tumorous tissue did not reveal a mutation. Our finding comprehends the previous study carried out by Alomar and colleagues which screened CTNNB1 gene in 60 colorectal cancer patients from Kingdom of Saudi Arabia (KSA) and revealed an activating mutation (S33F) in one of the tumor samples [52]. Our observations also analyzed the grade of β-catenin protein of the CTNNB1 gene in colorectal cancer in Pakistani population.…”
Section: Discussionsupporting
confidence: 88%
“…As a potential genetic mechanism for ß-catenin nuclear accumulation, Alomar et al identified an activating mutation in exon 3 of CTNNB1 (ß-catenin) gene which resulted in an amino acid change at phosphorylation sites of glycogen synthase kinase-3 (GSK-3β). Failing of phosphorylation was found to decrease sequestration of β-catenin by APC [28]. This effect might explain our finding with low APC mutational frequency but at the same time surprising high rate (29%) of nuclear ß-catenin positivity.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, the ΔN(89)-β-catenin mutant mimics the regulation intrinsic to AR-hypomorphic β-TrCP-knockdown lines. We additionally studied ΔN(47)-β-catenin—a mutant with altered regulation similar to ΔN(89)-β-catenin—that has been recorded in cancers (Alomar, et al, 2016), and the point mutant S33Y that inhibits β-TrCP-binding to β-catenin. S33Y—and similar mutations are found in pilomatricomas (Chan, et al, 1999), SW48 colorectal cancer cells (Sparks, et al, 1998) and hepatocarcinomas (Zucman-Rossi, et al, 2006).…”
Section: Resultsmentioning
confidence: 99%